2020
DOI: 10.1111/hel.12690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics during vonoprazan‐containing triple therapy on gut microbiota in Helicobacter pylori infection: A randomized controlled trial

Abstract: | INTRODUC TI ONHelicobacter pylori infection of the gastric epithelial mucosa affects approximately 50% of the population worldwide. In developing countries, H pylori infection has been observed in more than 90% of the population because this infection remains asymptomatic in early childhood, resulting in an enormous economic burden on healthcare resources. 1,2 Standard triple antibiotic therapy (proton-pump inhibitor (PPI) in combination with two of the following: amoxicillin, clarithromycin, or metronidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…Alternatives to triple eradication therapy include bismuth quadruple therapy, concomitant therapy, sequential therapy, 4 and recently introduced vonoprazan therapy 58,59 . While concomitant and bismuth quadruple therapy have showed long‐term perturbations of the gut microbiome, 47 vonoprazan therapy supplemented by probiotics has been shown to improve the rate of eradication and potentially aids the maintainment of species diversity within the gut microbiome 60 . Although a number of studies have identified vonoprazan as effective eradication strategy, 59‐61 study evaluating the effect of vonoprazan monotherapy on the gut microbiome revealed stimulated lipopolysaccharide biosynthesis thus increasing the risk of enteric infection 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatives to triple eradication therapy include bismuth quadruple therapy, concomitant therapy, sequential therapy, 4 and recently introduced vonoprazan therapy 58,59 . While concomitant and bismuth quadruple therapy have showed long‐term perturbations of the gut microbiome, 47 vonoprazan therapy supplemented by probiotics has been shown to improve the rate of eradication and potentially aids the maintainment of species diversity within the gut microbiome 60 . Although a number of studies have identified vonoprazan as effective eradication strategy, 59‐61 study evaluating the effect of vonoprazan monotherapy on the gut microbiome revealed stimulated lipopolysaccharide biosynthesis thus increasing the risk of enteric infection 62 .…”
Section: Discussionmentioning
confidence: 99%
“…58,59 While concomitant and bismuth quadruple therapy have showed longterm perturbations of the gut microbiome, 47 vonoprazan therapy supplemented by probiotics has been shown to improve the rate of eradication and potentially aids the maintainment of species diversity within the gut microbiome. 60 Although a number of studies have identified vonoprazan as effective eradication strategy, [59][60][61] study evaluating the effect of vonoprazan monotherapy on the gut microbiome revealed stimulated lipopolysaccharide biosynthesis thus increasing the risk of enteric infection. 62 In general, adverse events are common in combinatorial therapies, thereof vonoprazan therapy accompanied by probiotics might be promising strategy in H pylori eradication, especially in regions with high resistance rates to clarithromycin.…”
Section: Influence Of Eradication Therapy On the Gut Microbiomementioning
confidence: 99%
“…Taxonomic profiles from a metagenomic study showed a decrease in the relative abundance of Bifidobacterium after therapy 54 . The decreased Bifidobacterium was confirmed in other studies 37,50,57,60 . However, another study illustrated that Bifidobacterium increased 6 months following successful eradication 9 .…”
Section: Gastrointestinal Microbiota Reshaping Upon Eradication Therapymentioning
confidence: 72%
“…To better answer this question, recruiting negative controls is recommended in future study design. Interestingly, the proof is emerging that probiotic supplementation can alleviate the perturbation in diversity and structure caused by antibiotics 55,59,60 . Probiotics, defined as live microorganisms that can provide health benefits when consumed, have been shown to stabilize microbiota and improve gastrointestinal symptoms 31,61 .…”
Section: Gastrointestinal Microbiota Reshaping Upon Eradication Therapymentioning
confidence: 99%
“…To date, the safety of H. pylori eradication therapy using proton-pump inhibitor and P-CAB in children is controversial. A previous study reported the effect of probiotics during vonoprazan-containing triple therapy on the intestinal microbiota in individuals with H. pylori infection [17]. However, only the intestinal microbiota before and immediately after eradication therapy were evaluated.…”
Section: Introductionmentioning
confidence: 99%